Revelatory events: three case studies of the emergence of new spiritual paths - Taves, Ann (Princeton University Press, 2016)
Making meaning -- Case study: a restored church -- Translation -- Materialization -- Beginnings -- Case study: an anonymous fellowship -- Stories -- Fellowship -- Seeking -- Case study: a course in miracles -- Emergence -- Teaching(s) -- Roles -- Creating paths -- Groups -- Selves -- Motives -- Discussion of methods